Evaluation of the amount of nanoparticles emitted in LASER additive manufacture/welding - Gomes, João (2019)
Objectives: The objective of this study was the evaluation of the professional exposure to nanoparticles during tasks performed in workstations for production of metallic parts by laser welding additive manufacturing.Materials and methods: The study was developed in an installed additive manufacturing machine, having controlled temperature and humidity in an industrial unit where metal parts were being produced using stainless steel powders of granulometry of 10 to 35m.Results and discussion: Monitoring of airborne nanoparticles emission was made using adequate equipment, which showed considerable number of nanoparticles over the baseline, having the same composition as the steel powder used.Conclusion: It is concluded that the values of professional exposure to nanoparticles are high in these workstations and that the nanoparticles to which the workers are exposed are small in size (around 15nm), thus having a strong capacity for alveolar penetration and, consequently, with a strong possibility of passing to the bloodstream, accumulating in the body.